Planning, control and monitoring tools for industrial garment assembly processes - Carvalho, Helder (2003)
Garment construction is a complex process due to the properties of the textile materials. Furthermore it still relies on human operators in most of the material handling and process monitoring. On the other hand, the set-up of the machines is still based on trial-and-error and empirical knowledge. Current market trends with higher demand on quality, shorter production runs and increasing variety of materials boost the economical significance of machine set-up and better process planning, monitoring and control. This paper presents the development of monitoring and control techniques aiming at the introduction of new tools to accomplish this. A sensor-based data acquisition and analysis system has been developed that enables a quick offline evaluation of the performance of the machine in several of its subsystems. Knowledge that has been gained from these measurements is the basis to develop CAE/CAM tools and real-time control devices